2021
DOI: 10.3389/fpls.2021.748750
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Genetic Diversity of Nordic Red Clover (Trifolium pratense) Revealed by SeqSNP-Based Genic Markers

Abstract: Red clover (Trifolium pratense) is one of the most important fodder crops worldwide. The knowledge of genetic diversity among red clover populations, however, is under development. This study provides insights into its genetic diversity, using single nucleotide polymorphism (SNP) markers to define population structure in wild and cultivated red clover. Twenty-nine accessions representing the genetic resources available at NordGen (the Nordic gene bank) and Lantmännen (a Swedish agricultural company with a red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 49 publications
7
38
3
Order By: Relevance
“…The lower values in the latter case are most likely because most of the SNP markers used were located within genes ( Enyew et al, 2021 ) and hence are expected to be less diverse than GBS-based SNP markers. Similar bi-allelic SNP-based studies in noug ( Guizotia abyssinica ; Tsehay et al, 2020 ) and red clover ( Trifolium pratense ; Osterman et al, 2021 ) reported Ho values of 0.24 and 0.22, respectively. It is expected that noug and red clover have higher Ho values than finger millet and sorghum because both of these crops are strictly outcrossing, enabling a higher level of heterozygosity.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The lower values in the latter case are most likely because most of the SNP markers used were located within genes ( Enyew et al, 2021 ) and hence are expected to be less diverse than GBS-based SNP markers. Similar bi-allelic SNP-based studies in noug ( Guizotia abyssinica ; Tsehay et al, 2020 ) and red clover ( Trifolium pratense ; Osterman et al, 2021 ) reported Ho values of 0.24 and 0.22, respectively. It is expected that noug and red clover have higher Ho values than finger millet and sorghum because both of these crops are strictly outcrossing, enabling a higher level of heterozygosity.…”
Section: Discussionmentioning
confidence: 63%
“…After seed germination, extra seedlings were removed, and only a single seedling was maintained for each accession. Three weeks after planting, the leaf tissue of each accession was separately sampled using the BioArk Leaf collection kit from LGC, Biosearch Technologies ( https://biosearchassets.blob.core.windows.net/assetsv6/guide_bioark-leaf-collection-kit.pdf ), as described in Osterman et al (2021) . Afterward, the samples were sent to LGC, Biosearch Technologies (Berlin, Germany) for genomic DNA extraction, followed by GBS-based genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…The modern tetraploid red clover cultivars (2n = 4x = 28) have been developed using autopolyploidy from diploid genotypes through chromosome doubling (Taylor and Quesenberry, 1996). The cultivated types of red clover had a similar level of genetic diversity, implying that modern red clover breeding programs did not negatively affect either genetic diversity or population structure (Osterman et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The accessions were planted and grown for two weeks in a greenhouse at the Swedish University of Agricultural Sciences (SLU, Alnarp, Sweden), as described in Osterman et al (2021). The BioArk leaf collection kit (LGC Biosearch Technologies) was used to collect ten 6 mm leaf discs (1 leaf disc/plant).…”
Section: Selecting Germplasm and Plantingmentioning
confidence: 99%
“…For instance, the publication of its reference genome (De Vega et al, 2015) has facilitated the discovery of quantitative trait loci (QTL) for various traits, and the "mining" of single nucleotide polymorphism (SNP) markers (Herrmann et al, 2008;Ergon et al, 2019;Li et al, 2019). In two recent papers on population genetics, SNPs were used to assess the population structure in individually genotyped red clover (Jones et al, 2020;Osterman et al, 2021). Jones et al studied 75 accessions from Europe, Asia, and Iberia where 70 were wild populations and five were commercially available breeding populations.…”
Section: Introductionmentioning
confidence: 99%